Rejection of Orientalis Argumentation About Textual Criticism of the Qur’an - Nurjannah Ismail; Cut Zaenab; Edi Darmawijaya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This research stems from accusation and unfounded criticism by orientalists regarding so many errors contained in the Qur’an from various aspects. Both in terms of historicity, originality, inconsistent variety of readings, the influence of Jewish and Christian on the teaching and verse of the Qur’an and even criticism of error in copying the text of the Qur’an. The purpose of this study is to explain the textual criticism of the Qur’an from an orientalist’s perspective, starting from their criticism of the history of the Qur’an and leading to accusations of error in copying the Qur’an, the second purpose is about the refutation of the idea and criticism conveyed by the orientalist. The method used in this research is descriptive qualitative with the type of research literature study. The theory used in this research for orientalist study is theory of textual criticism and the philological approach as a method of copying the Qur’an. Based on the research that has been done, the results obtained are: firstly, regarding the criticism of the Qur’an by orientalist, it focus on the authenticity of the Qur’an which they consider to be fake. Refutation of orientalist’s arguments, as Muslim scholars does. For example, Mustafa A'zami said that orientalist only felt defeated when they found out that their holy book was no longer original and had undergone many changes. The purpose and mission of the missionaries to find out the weakness of Muslim is also one of the objections that can be put forward because with this mission and purpose, orientalist studies of the Qur’an are no longer objective. Based on the result of this study, the author suggest for Muslim to read more Islamic literature so that they can maintain their faith and continue to believe that the Qur’an is the holy word of God.